The new fresh seafood buyer's guide : a manual for distributors, restaurants, and retailers / Ian Doré - Doré, Ian
This book is a completely new edition of Fresh Seafood-The Commer cial Buyer's Guide, which was first published in 1984. There have been many changes in both product and the seafood business in the intervening years. About 70 percent of the material in this book is new, a tribute to the rapid pace of change throughout the industry. The subject of this book is fresh seafood. "Fresh" is defined as product handled under refrigeration (mechanical or ice) from har vester to consumer. This excludes frozen product, canned product and other shelf-stable packaging. Frozen seafoods are covered in the companion volume, The New Frozen Seafood Handbook. Many prod ucts are, of course, handled in both refrigerated and frozen forms.